(untitled) (Research, Society and Development, 2022)
Objective: To analyze the main clinical evidence of stem cell therapy in the healing of burns. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “stem cell”, “hematopoetic stem cells’”, “embryonic stem cell”, “burn”, “burned” and “burn units”. Full texts, available in Portuguese, English or Spanish, published between January 2005 and April 2022 were included; human studies (clinical studies). Results: Four articles made up the final sample of this review, with publication frequency between 2005 and 2022. In total, 328 burn patients were treated with stem cells. The therapy showed positive results in terms of faster wound healing, lower rate of infection and complications, higher survival rate and faster hospital discharge. Conclusion: It was found that stem cell therapy in burn patients can increase the effectiveness of local treatment and improve surgical skin restoration. However, more clinical trials need to be encouraged in order to more accurately justify the use of this therapy in these patients.